Joint Effects Of Distinct Biotic Interactions And Dispersal On A Multi-species Ecological System - Bello Aliyu, Murtala (2021)
One of the central questions in ecology is how do we maintain community stability and species coexistence mechanisms in a complex ecological community. It is thought that the interplay between mutualism, competition, predation and local dispersal support multi-species coexistence. In this thesis, we re-formulate a four-species multiple interactions type (e.g., resource-competitor-exploiter-mutualist) system by incorporating a spatial diffusion term to model local dispersal process. We then employ this model to assess how the dynamics of dispersal, mutualism and competition shape species coexistence and community stability in this ecological system. Our findings show that the interplay of mutualism and competition affects the complexity of ecological dynamics in this multiple interactions type system with local dispersal. Using numerical simulation, we demonstrate how strong mutualism could stabilize the dynamics of this multi-species community. Employing bifurcation analysis, we also discover that mutualism essentially modifies this ecological community’s response to increasing competitive pressure on the resource species. These insights are evident in our findings through the emergence of intriguing dynamics and various bifurcations (e.g., subcritical and supercritical Hopfs, transcritical, saddle-node, transcritical-Hopf and homoclinic bifurcations).